Mesenchymal stromal cells for bone trauma, defects, and disease: Considerations for manufacturing, clinical translation, and effective treatments - Annie C. Bowles-Welch; Angela C. Jimenez; Hazel Y. Stevens; David A. Frey Rubio; Linda E. Kippner; Carolyn Yeago; Krishnendu Roy (Bone Reports, 2023)
Bone is a complex tissue capable of natural repair to injury, however, the healing process is often impaired by the untoward effects of trauma, defects, and disease. Thus, therapeutic modalities, including the use of cells involved in the body's natural healing processes, are investigated to promote or complement natural bone repair. Herein, several modalities and innovative approaches for using mesenchymal stromal cells (MSCs) to treat bone trauma, defects, and diseases are discussed. Given the evidence that supports the promising potential of MSCs, we highlight important considerations for advancing the clinical use of MSCs including the standardization of procedures from the harvest to delivery to patients and realized solutions to manufacturing. A better understanding of the current approaches implemented to address the challenges of using therapeutic MSCs will help improve study designs and, ultimately, achieve effective outcomes for restoring bone health.